Η χρήση πληροφοριακών συστημάτων ERP στην διαχείριση εφοδιαστικής αλυσίδας στους λιμένες. Μοντελοποίηση και προσομοίωση του συστήματος. - ΜΠΑΛΤΑΣΗΣ, ΑΝΑΣΤΑΣΙΟΣ (Πανεπιστήμιο Πελοποννήσου, 2024)
This paper seeks to investigate the implementation and use of Enterprise Resource Planning (ERP) and Logistics systems in Greek ports, analyzing in detail the benefits, challenges and prospects arising from the use of these systems. ERP and Logistics systems are essential management and process automation tools for modern businesses, as they allow for the integrated management of all functions of an organization through a single system. In particularly large and complex operations such as ports, the use of ERP and Logistics can have significant benefits in terms of simplifying and optimizing processes, reducing costs and increasing productivity. However, the implementation of these advanced systems requires significant investments and changes in port operations. Proper planning and training of staff, adaptation of legislation, interoperability between systems and a sound technical infrastructure are necessary. In addition, cooperation between stakeholders is an essential prerequisite for the correct implementation of ERP and logistics systems. The paper first focuses on the description and characteristics of ERP (Enterprise Resource Planning) systems. Through a survey, the challenges and opportunities of using Enterprise Resource Planning are identified. Finally, by using modeling, the functions of ERP are represented and different scenarios and results in the operation a port are studied. Keywords: ERP, Modelling and Simulation, Efficiency, Logistics
Μ.Δ.Ε. 63
Keywords: ERP; ΛΙΜΕΝΕΣ; Μοντελοποίηση και προσομοίωση του συστήματος ERP